Sexual dysfunction as a consequence of coronavirus infection and quarantine due to the COVID-19 pandemic - N. D. Kibrik; Yu. P. Prokopenko (Лечащий Врач, 2021)
The article examines the factors associated with the COVID-19 pandemic, affecting intimate life in long-term couples. Research by sexologists, psychologists, psychotherapists, reproductologists, combining versatile manifestations of self-esteem and relationships in the intimate sphere demonstrate a fairly harmonious picture of phenomena associated with psychological, mental and physiological needs and capabilities of both individuals and macrosocial formations. The dependence of manifestations of sexuality on the intensity of the infectious situation and quarantine policy is noted. Practical approaches are proposed to stabilize and improve intimate behavior in married couples living in limited conditions in the presence of other family members, aimed at reducing the risk of depression and sexual dysfunction in self-restraint conditions in the COVID-19 pandemic. Currently, after the winter of 2020-2021, accompanied by a progressive decrease in the level of morbidity and mortality, the number of people with a rational attitude to what is happening is growing, who are actively adapting within the family, as well as in society.